2021
DOI: 10.1126/sciadv.abh0319
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable Nanobody (PiN-21) prevents and treats SARS-CoV-2 infections in Syrian hamsters at ultra-low doses

Abstract: Globally, there is an urgency to develop effective, low-cost therapeutic interventions for coronavirus disease 2019 (COVID-19). We previously generated the stable and ultrapotent homotrimeric Pittsburgh inhalable Nanobody 21 (PiN-21). Using Syrian hamsters that model moderate to severe COVID-19 disease, we demonstrate the high efficacy of PiN-21 to prevent and treat SARS-CoV-2 infection. Intranasal delivery of PiN-21 at 0.6 mg/kg protects infected animals from weight loss and substantially reduces viral burden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 60 publications
3
102
0
Order By: Relevance
“…Nanobody therapeutics derived from camelid antibodies has advantages relative to conventional antibodies. Although several studies have reported nanobody drug candidates that specifically target SARS-CoV-2 ( Huo et al, 2020 ; Hanke et al, 2020 ; Xiang et al, 2020 ; Schoof et al, 2020 ; Wrapp et al, 2020a ; Pymm et al, 2021 ; Nambulli et al, 2021 ), as of this writing, only two studies have evaluated their nanobody drug candidates in an animal model for anti-SARS-CoV-2 therapeutic efficacy ( Pymm et al, 2021 ; Nambulli et al, 2021 ). None of these studies have evaluated their nanobody drug candidates for in vitro thermostability, in vivo stability, or tissue biodistribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanobody therapeutics derived from camelid antibodies has advantages relative to conventional antibodies. Although several studies have reported nanobody drug candidates that specifically target SARS-CoV-2 ( Huo et al, 2020 ; Hanke et al, 2020 ; Xiang et al, 2020 ; Schoof et al, 2020 ; Wrapp et al, 2020a ; Pymm et al, 2021 ; Nambulli et al, 2021 ), as of this writing, only two studies have evaluated their nanobody drug candidates in an animal model for anti-SARS-CoV-2 therapeutic efficacy ( Pymm et al, 2021 ; Nambulli et al, 2021 ). None of these studies have evaluated their nanobody drug candidates for in vitro thermostability, in vivo stability, or tissue biodistribution.…”
Section: Discussionmentioning
confidence: 99%
“…The series may also be developed to become part of cocktail therapies that target multiple sites on SARS-CoV-2. Third, despite its rapid clearance from the blood, Nanosota-1C could be used as an inhaler to treat infections in the respiratory tracts ( Van Heeke et al, 2017 ; Nambulli et al, 2021 ) or as an oral drug to treat infections in the intestines ( Vega et al, 2013 ). The worldwide distribution of COVID-19 in the world calls for the large-scale manufacturing of anti-SARS-CoV-2 therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the high preclinical efficacy of an ultrapotent Nb construct (PiN-21) has been demonstrated in a sensitive COVID-19 animal model. At a very low dose (0.2 mg/kg), the PiN-21 inhalation treatment quickly protects animals' weight loss after SARS-CoV-2 infection, decreases lung viral titers by a million fold which leads to drastically mitigated lung pathology, while preventing viral pneumonia 14 . Potent neutralizing Nbs, therefore, represent a convenient and cost-effective therapeutic option to help mitigate the evolving pandemic.…”
mentioning
confidence: 99%
“…Recently, mice challenged intranasally with SARS-CoV-2, and then treated prophylactically IP with a nanobody Fc fusion has also been shown to reduce viral load in the lungs 17 . More recently, Nebulli et al 18 , showed that nasal administration of a nanobody 6 h after viral challenge also reduced viral load and weight change in the Syrian hamster model. Our data are consistent with these results but our treatment with the C5 trimer 24 h after viral challenge when the clinical manifestations of disease rst become apparent is a more demanding test of nanobody e cacy and arguably a more realistic model of therapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, while conventional antibodies that comprise two disulphide-linked polypeptides, heavy and light chain, typically require mammalian cells for production, nanobodies can be manufactured using readily available microbial systems. The potency of nanobodies against SARS-CoV-2 7 infection has been demonstrated in cell-based assays [8][9][10][11][12][13][14][15][16] and most recently in animal studies 17,18 . Several strategies for engineering VHH into a multivalent species are known.…”
Section: Read Full License Introductionmentioning
confidence: 99%